Description of Numeracy Literacy Skills in Science Learning - Salma Samputri; Rifda Nur Hikmahwati Arif (Universitas Muhammadiyah Enrekang, 2024)
This research is a descriptive study with a quantitative approach with a survey method to describe the numeracy literacy skills of each question answered by 7th grade students of SMP IT wahdah islamiyah Makassar. The purpose of this study was to determine the level of numeracy literacy skills of 8th grade students at SMP IT Wahdah Islamiyah Makassar. The population of this study were all 8th grade students at SMP IT Wahdah Islamiyah Makassar consisting of 3 classes with a total of 89 students. The sample was selected using saturated sampling technique so that the determination of the sample when all members of the population were used as samples and the number of research samples was 89 students. The research instrument is a numeracy literacy test instrument totaling 14 questions. The data collection technique is by giving tests directly. Data were analyzed using descriptive statistical analysis techniques. Based on the results of the analysis it can be concluded that the level of numeracy literacy skills of students has an average value of 30.34 fsn is in the low category.